Decoding brand perception through online customer reviews: A comparative study across geographical locations - Holm, Gabriella Märta Kristina (2024)
Dissertation presented as the partial requirement for obtaining a Master's degree in Data Driven Marketing, specialization in Digital Marketing and Analytics